Microwave-Assisted Synthesis of Poly(ε-caprolactone)-block-poly(ethylene glycol) and Poly(lactide)-block-poly(ethylene glycol) - Karagoz, Ayse; Dincer, Sevil (WILEY-V C H VERLAG GMBH, 2010)
This study reported the preparation and characterization of PCL-b-mPEG (poly(epsilon-caprolactone)-block-poly(ethylene glycol)) and PLL-b-mPEG (poly(L-lactide)block-poly(ethylene glycol)) diblock copolymers by microwave heating and comparison of resulted products the ones with prepared by conventional heating. Diblock copolymers were synthesized successfully by the microwave-assisted ROP in the presence of stannous octoate (SnOct(2)) as catalyst under nitrogen atmosphere in different monomer ratios. Structural and functional characterization of copolymers were performed by FTIR, (1)H-NMR and DSC. Molecular weight values were determined by GPC and also calculated from (1)H-NMR. According to the results, microwave irradiation allowed to obtain polymers with very narrow size distribution in very short reaction time. Similar polymers prepared by conventional heating were also synthesized for comparison. Molecular weight and conversion of polymers were increased by irradiation time. This change was continued until a certain time point after which no more increase was observed. It was concluded that microwave irradiation is a succesful method to obtain these diblock copolymers in very short reaction time and with a similar conversion obtained by conventional method.
Keywords: diblock copolymers; microwave heating; PCL-b-mPEG; PLL-b-mPEG; ring-opening polymerization; IRRADIATION; COPOLYMERS; TRIBLOCK; Polymer Science